2019
DOI: 10.1016/j.adhoc.2019.101988
|View full text |Cite
|
Sign up to set email alerts
|

Non-interactive zero knowledge proofs for the authentication of IoT devices in reduced connectivity environments

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 41 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Increasing the number of questions to 5 bits reduces the number of rounds to 8 [34,36]. Feige-Fiat-Shamir protocols are used in smart cards [37,38], the Internet of Things [39], and RFID automatic object identification systems [40,41] due to their high imitability. In reference [42], it was shown that the use of Feige-Fiat-Shamir ZKAP in IoT devices provides high imitability with the use of a 20-bit key and 20 rounds of authentication.…”
Section: Zero-knowledge Authentication Protocols: Advantages and Disadvantagesmentioning
confidence: 99%
“…Increasing the number of questions to 5 bits reduces the number of rounds to 8 [34,36]. Feige-Fiat-Shamir protocols are used in smart cards [37,38], the Internet of Things [39], and RFID automatic object identification systems [40,41] due to their high imitability. In reference [42], it was shown that the use of Feige-Fiat-Shamir ZKAP in IoT devices provides high imitability with the use of a 20-bit key and 20 rounds of authentication.…”
Section: Zero-knowledge Authentication Protocols: Advantages and Disadvantagesmentioning
confidence: 99%
“…Examples of other uses, include Hypothesis Testing based algorithms to perform polling for the values of multiple KPIs in an fig based IoT sensor network [6] , to facilitate protocols for the authentication of IoT devices [7] or manage the privacy of Smart Energy Meters [8]. To our knowledge, no other hypothesis-based application for evaluating different mitigation strategies in IoT has been presented in the available literature.…”
Section: A Statistical Hypothesis Testing In the Context Of Iot Networkmentioning
confidence: 99%
“…Hence, the result of malicious attacks can have severe consequences on human lives, business productivity and national security. In the following, we highlight some of the key security threats to CPS; we refer interested readers to the following works [3,5,9,20,32] for an extensive treatment of the topic.…”
Section: Cps Security Threats and Motivationmentioning
confidence: 99%